The Effect of Feeding Feed Containing of Soybean Residue Fermented byAspergillus niger on the Quality of Gallus Domesticus’ Egg Interior - Rika Marwati; Azhari A; Ismail I (Jurnal Medika Veterinaria, 2014)
The aim of this research was to find out the egg is interior quality of Gallus domesticus fed with soybean residue fermented by Aspergillus niger. The study used fifteen productive hens with the age of 15-16 months. The hens then devided into three treatment groups, 5 hens each. Thisstudy was conducted using Completely Randomized Design. The feed used in this research was 324-2 commercial food. Group I (P0) as controlgroup was fed with 100 g commercial food daily, Group II (PI) was fed with 85 g commercial food added with 10 g of soybean nonfermentedresidu daily, and Group III (PII) was fed with 10 g of fermented soybean residu. The eggs were examined on the third day of treatmen until 30eggs/treatment. The average (SD) of native chicken egg yolk index in group P0, PI, and PII were 0.438±0.037, 0.444±0.040, and III 0.463±0.041,respectively. The result showed that egg yolk index of native of chicken fed with Aspergillus niger effect significantly (P0.01) on egg yolk indeksof native chicken fed with nonfermented soybean and control. The average of native chickens egg yolk Haugh unit on P0, PI, PII were60.16±28.39, 75.23±9.25, and 76.33±7.52, respectively. In conclusion, Haugh unit of native chicken eggs fed with soybean residu fermented withAspergillus niger effect significantly on (P0.05) control group.____________________________________________________________________________________________________________________Key words: soybean residue, Aspergillus niger, layer, Haugh unit, index yolk